Report...on the implementation of the participation programme and emergency assistance (UNESCO [Paris]FR, 2008)
List projects approved for Member States and Associate Members, together with the amounts approved to finance them. Lists also, projects approved for international non-governmental (NGOs) maintaining official relations with UNESCO, together with the amounts approved to finance them.
Keywords: PROJECT FINANCING